Different shapes of microstrip line design using FR4 substrate materials – A comprehensive review. (2021) - Harikirubha, S.; Baranidharan, V.; Saranya, S.; Keerthana, K.; Nandhini, M.
Abstract: Microstrip line plays a prominent role in the field of RF engineering. Reduced size and easy fabrication criterion of microstrip line are the main reason for its increased usage. In this paper the usage of microstrip lines as different element such as filter, resonator, phase shifter, performance enhancer for different microwave elements was discussed. This paper reviews the usage of different shapes of microstrip lines for different applications. Comparison is made for operating frequency, substrate used, applications and shapes. The Simulated S parameter results are also shown in this paper.